Perspektywy projektowania celów doradztwa zawodowego w systemie edukacyjnym - Rosalska, Małgorzata (Wydawnictwo Naukowe UAM, 2013)
The article concerns the basic perspectives of constructing objectives of career counselling. The reference point is counselling solutions used in the educational system. Four ways of thinking about key objectives of counselling activities in schools are discussed. These are: the perspective of developmental tasks, the perspective of pupil’s situational problems, the perspective of the labour market and counselling process. The aim of the article is also to indicate the risk of overestimation of the importance of the structure and dynamics of changes in the labour market in creating counselling support for pupils.
Perspectives in creating objectives of career counselling in the educational system
Keywords: caree counselling; counselling support for pupils; objectives of counselling activities